Numerical simulation of entropy generation for nanofluid with the consequences of thermal radiation and Cattaneo-Christov heat flux model. (October 2022) - Waqas, Hassan; Fida, Muzamil; Liu, Dong; Manzoor, Umair; Muhammad, Taseer
Abstract: Nanofluids have attracted a lot of attention as a result of their various manufacturing, technical, and medical purposes. The current investigation looks at the usage of Casson nanofluid in a permeable solar collector flow on an indefinite surface. Copper oxide-water ( CuO − H 2 O ), titanium dioxide-water ( TiO − H 2 O ), and disulfide molybdenum-water ( MoS 4 − H 2 O ) nanofluids outcomes were all evaluated and expounded on as well. Copper oxide ( CuO ) nanoparticles have more elevated heat conductivity than titanium dioxide ( TiO ) nanoparticles, the Copper oxide-water ( CuO − H 2 O ) nanofluid demonstrated better heat transport capability than titanium dioxide-water ( TiO 2 − H 2 O ) nanofluid. As the values of various parameters improve, the velocity, temperature, and entropy profiles of specified fluids grow and decrease, as shown in the graphical depictions. Using appropriate similarity adjustments, the governing partial differential equations were converted into nonlinear ordinary differential equations. The shooting technique is used in conjunction with the MATLAB software included with the bvp4c to compute a highly nonlinear system of equations. Graphs show the effects of key factors on velocity and temperature concentration. The temperature profile rises as shape factors rise. The temperature panel is decreasing as the Cattaneo-Christov component increases. By increasing the influence of the Biot number, both temperature and entropy profiles are rising. The conclusions for Casson nanofluid are analyzed using the parameterized development of the Cattaneo-Christov component. These findings are helpful for the thermic control of heat transmission in upcoming technologies. Finally, the dynamics of fluid flow are investigated using streamlines.